Biosilicate®–gelatine bone scaffolds by the foam replica technique: development and characterization - Desimone, Deborah; Li, Wei; Roether, Judith; Schubert, Dirk W.; Crovace, Murilo; Rodrigues, Ana; Zanotto, Edgar; Boccaccini, Aldo R. (Science and Technology of Advanced Materials, 2013)
The development of bioactive glass-ceramic materials has been a topic of great interest aiming at enhancing the mechanical strength of traditional bioactive scaffolds. In the present study, we test and demonstrate the use of Biosilicate® glass-ceramic powder to fabricate bone scaffolds by the foam replica method. Scaffolds possessing the main requirements for use in bone tissue engineering (95% porosity, 200–500 μm pore size) were successfully produced. Gelatine coating was investigated as a simple approach to increase the mechanical competence of the scaffolds. The gelatine coating did not affect the interconnectivity of the pores and did not significantly affect the bioactivity of the Biosilicate® scaffold. The gelatine coating significantly improved the compressive strength (i.e. 0.80 ± 0.05 MPa of coated versus 0.06 ± 0.01 MPa of uncoated scaffolds) of the Biosilicate® scaffold. The combination of Biosilicate® glass-ceramic and gelatine is attractive for producing novel scaffolds for bone tissue engineering.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.biosil
Keywords: bioactivity; bone tissue engineering; glass-ceramics; scaffolds